Eccentric views on money and banking - Quah, Chee Heong (University of Malaya Press, 2016)
The author sets out to show why conventional economic policies aimed at curtailing boom-bust economic cycles are pretty hopeless. Instead he suggests alternative remedies which not only could be applied more profitably to national economies but also to the more mundane dealings of everyday life.